2013
DOI: 10.1002/bit.24891
|View full text |Cite
|
Sign up to set email alerts
|

An ultra scale‐down approach to study the interaction of fermentation, homogenization, and centrifugation for antibody fragment recovery from rec E. coli

Abstract: Escherichia coli is frequently used as a microbial host to express recombinant proteins but it lacks the ability to secrete proteins into medium. One option for protein release is to use high-pressure homogenization followed by a centrifugation step to remove cell debris. While this does not give selective release of proteins in the periplasmic space, it does provide a robust process. An ultra scale-down (USD) approach based on focused acoustics is described to study rec E. coli cell disruption by high-pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…We have demonstrated that stress minimization by decreasing culture temperature and inducer concentration can be used to improve not only recombinant protein yields and folding but also correct subcellular targeting and overall cell integrity for subsequent cell harvest and protein release steps . Careful balancing of increases in inducer concentration and decreases in growth and induction temperature allowed optimization of Fab D1.3 yield.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have demonstrated that stress minimization by decreasing culture temperature and inducer concentration can be used to improve not only recombinant protein yields and folding but also correct subcellular targeting and overall cell integrity for subsequent cell harvest and protein release steps . Careful balancing of increases in inducer concentration and decreases in growth and induction temperature allowed optimization of Fab D1.3 yield.…”
Section: Discussionmentioning
confidence: 99%
“…In order for periplasmic release to succeed, bacterial viability and physical integrity must be maintained upon harvest. Metabolic stress in bacteria generating recombinant proteins such as periplasmically‐targeted Fab fragments can cause cell lysis during fermentation or fragility leading to lysis during cell harvesting in industrial centrifuges or subsequent processing steps . This eliminates the advantages of periplasmic expression as cytoplasmic proteins, membrane components and DNA are all released, complicating subsequent purification of the target recombinant protein.…”
Section: Introductionmentioning
confidence: 99%
“…Baumann et al and Ladd Effio et al used a parallelized system for eight samples with volumes between 1 and 5 mL for quantitative comparison of high‐throughput upstream screenings. Wenger et al and Li et al describe adaptive focused acoustics (AFA) as an advanced sonication method. Higher frequencies lead to shorter acoustic cycles resulting in reduced time for bubble growth and therefore smaller bubbles with improved mixing .…”
Section: Disruption Techniquesmentioning
confidence: 85%
“…The extent of cell disruption and the method itself affect the composition and biophysical and biochemical properties of the homogenate such as viscosity, density, particle size distribution, host cell protein, host cell DNA and endotoxin level. These properties in turn impact the subsequent purification steps such as centrifugation , filtration and chromatography and finally the result of the whole purification process chain .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation